Analisis Sistem Informasi Pengelolaan Data Alumni MAN Labuhanbatu Berbasis Codeigniter PHP Framework - Muhammad Adlin Hasibuan; Syaiful Zuhri Harahap; Marnis Nasution (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
Alumni data management information system is a platform designed to manage and maintain alumni data effectively and efficiently. This system makes it easy for educational institutions to collect, store, and manage information about their graduates, such as personal data, education history, career, and their contribution to the alumni community. Using database technology and specialized software, the system enables fast data retrieval, organized data storage, and real-time monitoring of alumni activities. The existence of this information system also helps in maintaining good relations between institutions and alumni, as well as supporting alumni programs such as reunion events, networking, and career development. In addition, the alumni data Management Information System serves as a strategic tool in improving the quality and reputation of educational institutions. Research on alumni data management information system analysis using the CodeIgniter PHP framework as a programming language is interesting to do. CodeIgniter PHP Framework is known as one of the lightweight and efficient frameworks in web application development, so it can provide advantages in managing complex alumni data.